2007
DOI: 10.1590/s1678-77572007000200009
|View full text |Cite
|
Sign up to set email alerts
|

Desensitizing bioactive agents improves bond strength of indirect resin-cemented restorations: preliminary results

Abstract: Objective:The aim of this study was to assess the bond strength of indirect composite restorations cemented with a resin-based cement associated with etch-and-rinse and self-etching primer adhesive systems to dentin treated or not with a bioactive material.Materials and Method:Twenty bovine incisor crowns had the buccal enamel removed and the dentin ground flat. The teeth were assigned to 4 groups (n=5): Group I: acid etching + Prime & Bond NT (Dentsply); Group II: application of a bioactive glass (Biosilicato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
13
1
8

Year Published

2011
2011
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 33 publications
(48 reference statements)
3
13
1
8
Order By: Relevance
“…In contrast to expectations, the use of Biosilicate® did not reduce conducted light, which could impede penetration of the adhesive system, even with the use of phosphoric acid in the conventional system [20]. In contrast, this study found a significant increase in bond strength resulting from the application of Biosilicate® prior to conventional adhesive and self-etching adhesive.…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…In contrast to expectations, the use of Biosilicate® did not reduce conducted light, which could impede penetration of the adhesive system, even with the use of phosphoric acid in the conventional system [20]. In contrast, this study found a significant increase in bond strength resulting from the application of Biosilicate® prior to conventional adhesive and self-etching adhesive.…”
Section: Discussioncontrasting
confidence: 99%
“…Under conditions similar to the present study, it has been observed that rubbing a Biosilicate® solution (0.5 g in distilled water in a 3:1 ratio) for 10 seconds on bovine dentin prior to the application of a conventional adhesive and a self-etching adhesive improved the bond strength values [20].…”
Section: Discussionsupporting
confidence: 78%
See 3 more Smart Citations